A continuidade do cuidado às crianças com condições crônicas egressas de terapia intensiva neonatal: a perspectiva das famílias - Tatiana Silva Tavares (2012)
The present study aimed to analyze the continuity of care for children with chronic conditions discharged from the Neonatal Intensive Care Unit (NICU) of a philanthropic hospital in the Brazilian state of Minas Gerais to have their care needs attended to. This is a qualitative research with a dialectical approach. The scenario comprised 14 households located in the Minas Gerais municipalities of Belo Horizonte, Contagem, Nova Lima, Ribeirão das Neves, Ibirité, and Sabará. The subjects were the mothers of 14 infants with chronic conditions. The inclusion criteria were that a childs relative should be the responsible for their care. For the definition of chronic condition were considered criteria based on their consequences on children's life. The kids were mean corrected age of one year and six months at the time of data collection. Data were collected through individual semi-structured interviews and application of Pediatric Evaluation of Disability Inventory. Interview data were analyzed using technique of Thematic Content Analysis. The results of the inventory were analyzed by normative scores, according to the adapted Brazilian version of the manual. The following empirical categories emerged: Trajectory of pregnancy to hospitalization in NICU, Chronic condition in childhood: limits and prospects, Domiciliary care for children with a chronic condition and The child with a chronic condition in the health care service. Data analysis of the first category revealed the complications in pregnancy and labour, and the mothers dissatisfaction with ante-natal and labour care. Aspects that facilitated the mothers experience were the possibility of staying in the hospital, the relationship established with the health professionals, and the information provided about the childs health. The second category revealed that the shock on being informed about the childs chronic condition was gradually overcome and followed by acceptance. Health professionals should consider the mothers needs to identify causes and receive explanations about the infants health condition. Although aware of the limitations inflicted by the chronic condition, the mothers recognized the childs progress and demonstrated perseverance and optimism. The third category revealed that home care is complex and diverse and that the period after hospital discharge was the most difficult. It revealed that the mother organized her life around the infants care and that the support of family and friends was essential. The fourth category evidenced the diversity of services and healthcare professionals needed to monitor the child. The access to those services was prompted by the health professionals referral or the mothers demand. Although it was possible to identify the network of services able to care for those childrens needs, such services were uncoordinated. The occurrence of aspects that facilitate the continuity of care, such as, the relationship with the health professionals, and the information provided about the childs health was however, irregular. The exacerbation of these childrens chronic condition was associated, mainly, to respiratory problems which demonstrate the importance of prevention and control programs. The study highlighted the importance of coordination between areas, such as social assistance, education, sports and leisure. It concludes that continuity of care for children with chronic conditions requires better integration and coordination of health services as well as the development of strategies to enable the communication between health professionals. Such strategy would enable the articulation of knowledge needed to the implementation of a comprehensive care. It is important to guarantee the mothers empowerment since they are present throughout those childrens care.